"Methodomania"? On the methodological and theoretical challenges of IMP business research. Issue 3 (17th October 2016) - Håkansson, Håkan; Waluszewski, Alexandra
Abstract : Purpose: Behind the simple connotation "business exchange" a complex empirical phenomenon can be observed, including using, producing and developing activities, taking place in different contexts, influenced by ideas stemming from both practice and mainstream economic thinking. The purpose of this paper is to discuss the methodological challenges of research on business exchange in general and of IMP research in particular. Furthermore, to discuss how the authors can avoid the contemporary "methodomania" trend, where the researchers' focus is directed toward accounting for which rules were followed. Design/methodology/approach: The paper is based on a methodological distinction made by Peter Galison (1997) in his investigation of the interdependence among research approach, methodology, and research object in microphysics. Studies based on: "image, " allows data in its original form, and "logic, " requires the translation of original data and therefore relies "fundamentally on statistical demonstrations." This distinction is utilized to investigate what is specific with business exchange as a research object, and how IMP researchers have dealt with the methodological challenges it presents. Furthermore, the paper considers these different methodological approaches in relation to theory and understanding of the research object. Findings: The main conclusion is the huge importance the image-based methodology has had for the development of the IMP network approach. From the very start the IMP project has been focused on the production of a large set of, in Galison's terminology, "hard facts" about the existence, substance and importance of interaction and the relationships it is creating. This image-based methodology has been utilized in the development of a set of imaging instruments, each with an ability to picture the content and consequences of business exchange. Research limitations/implications: Two methodological challenges which are specific for business research are identified. One is that "images" in terms of personal accounts on the organizing of production and use of economic resources are marbled with ideas, stemming from a mix of theories, textbooks and practice on how to do this. The second is that established theories create a "logic" in terms of the combination of "assumptions" and established "accounting principles" that produce a number of outputs interpreted as primary data and objective accounts of the characteristics of the production and use of economic resources. Practical implications: IMP's image-based methodology and the development of specific imaging instruments can increase the exactness in the pictures of the content and consequences of business interaction, and also, catch the range of its substance. Considering this circumstance could be a way to avoid "methodomania" and to breed awareness of the relationship among research object, methodology, and research approach. Social implications: IMP's image-based methodology can increase the awareness that the logic-based model of business exchange has been ascribed an advisory role in terms of how companies should act in order to survive and prosper: as sellers and buyers in relation to each other, and also in relation to others. Originality/value: First, the paper underlines that image-based methodologies can be used to produce "hard facts" about the existence, substance, and importance of business interaction. Second, the paper shows how the methodology of mainstream economics tends to be "the elephant in the room, " both in approaches resting on "image" and "logic." It addresses the importance of making the elephant visible and investigates what is happening in its shadow.